The genome sequence of the Broad Centurion soldierfly, Chloromyia formosa (Scopoli, 1763) [version 1; peer review: 2 approved] - Olga Sivell; Duncan Sivell (Wellcome Open Research)
We present a genome assembly from a male specimen of Chloromyia formosa (Broad Centurion soldierfly; Arthropoda; Insecta; Diptera; Stratiomyidae). The genome sequence has a total length of 790.81 megabases. Most of the assembly (98.79%) is scaffolded into 7 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled, with a length of 17.69 kilobases.